Laporan Kasus: Upaya Meningkatkan Asupan Zat Gizi pada Pasien Malnutrisi dengan Chronic Kidney Disease Stage V yang Menjalani Hemodialisis: Case Report: Efforts to Increase Nutrient Intake in a Malnourished Patient with Stage V Chronic Kidney Disease on Hemodialysis - Esmiati, Catur Endri; Najiyah, Mufliha; Dewi, Mira (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Chronic kidney disease (CKD) stage V is a terminal condition that requires renal replacement therapy and optimal nutritional intervention. Malnutrition is commonly found in patients with CKD undergoing hemodialysis and may worsen clinical outcomes. This case report aims to describe the role of nutritional intervention in a malnourished patient with CKD stage V. The patient was a 55-year-old individual with CKD stage V complicated by uremia, hypertensive heart disease (HHD), pneumonia, pleural effusion, tuberculosis, type 2 diabetes mellitus, anemia, and dyspepsia, and was at risk of malnutrition based on a Malnutrition Screening Tool (MST) score of 3 and Subjective Global Assessment (SGA) category B. Nutritional care was provided during three days of hospitalization using the Nutrition Care Process approach, including nutritional assessment, diagnosis, intervention, and monitoring and evaluation. The intervention consisted of a diabetic dialysis diet along with nutrition education and counseling. The results showed an improvement in nutrient intake and clinical condition, although intake did not reach ≥80% of the estimated requirements. Nutritional intervention plays an important role in supporting clinical improvement in patients with CKD stage V with comorbidities.